Design and Build a Holomatrix-Based Tactical Combat Simulation Application - Galih Ashari Rakhmat; Rizki Fauzian (Institut Teknologi dan Bisnis Bina Sarana Global, 2022)
The application of Holomatrix-based information technology advances in the training process as a form of training technology system innovation model to meet the challenges of future tasks, training systems in the military environment, must be implemented in order to be able to provide realistic training in accordance with the description of the actual operating field. In this study, a Holomatrix-based Tactical Combat Simulation Application has been designed that can be used by every member of the various branches of the military, especially the Indonesian Army. The system built and upgraded will provide troops with an overview of modern Holomatrix-based simulations. By using a computer that is able to evoke a three-dimensional atmosphere so that it can display as if it were a physical 3D image. The modern Holomatrix-based simulation will be used to train Tactical Decision Making Procedures (PPKT) and subordinate commanders to map and model yudha so that they can provide an overview of the actual operating field. After testing, it was found that this simulation application can be used as a tactical training tool, where each military branch involved can coordinate properly as it is done in real combat.